Optimalisasi Kesehatan Masyarakat Payum Melalui Skrining TBC dan Deteksi Dini PTM di Kabupaten Merauke: Penelitian - Eunike Adonia Laga; Brigita Suni; Mohammad Saljan; Laili Nur Hidayati; Bekti Sukoco; Endah Purwanti; Ade Ragil Wibowo; Siti Asma Kuniyati Laitupa; Devvyta Ferika Sari; Astrida Rakhma; Santa Sihombing (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Tuberculosis (TB) and non-communicable diseases (NCDs) such as hypertension and diabetes mellitus remain major public health burdens in remote communities. Samkai Village, Merauke Regency, faces limited access to active health screening, resulting in many undetected cases. This community service aimed to optimize the health status of the Payum community through integrated TB screening and early detection of NCDs. A one-stop community-based health post was implemented, combining sputum smear examination, blood pressure measurement, blood glucose and cholesterol testing, health education, and an active referral system. The activity was conducted in November 2025 involving 65 participants. Of the 25 adequate sputum samples examined, 12 participants (18.5% of total participants) were smear-positive for TB. In addition, 30 participants (46.2%) were identified with hypertension and 3 (4.6%) with dyslipidemia. A total of 45 participants were referred to the primary health center for further management. This program demonstrates that an integrated community-based screening approach is effective in uncovering hidden disease burden and linking communities with formal health services.